Black Spot Location Identification for National Highway: A Case Study of Mugling – Kotre Section of Prithivi Highway of Nepal - Gurung, Rajan; Aryal, Rajendra; KC, Narayan; Joshi, Buddhi Raj (Journal of Engineering Technology and Planning, 2023)
The rapid development of road infrastructure enhances connectivity and at the same time increases road crashes. A road traffic accident is one of the leading causes of injury and death in Nepal that has a great impact on the country’s economy. The identification of frequent road traffic crash spots and their causes are essential for the implementation of the most efficient countermeasures. Accident black spots are high-risk spots where numbers of accidents take place frequently and repeatedly. The study focused on the identification of black spots on the Mugling-Kotre section of the Prithivi highway of Nepal to provide knowledge for possible preventive measures for the improvement of road safety. The weighted severity index (WSI), prioritization index (PI), and focus group discussion have been performed to evaluate the safety status in the proposed area. The accident data were analyzed based on the weighted severity index (WSI), and the prioritization index (PI) was estimated by assigning a suitable weight to the factors contributing to an accident. Based on these results, six accident spots have been found critical regarding traffic safety. The result obtained from WSI and PI was further evaluated based on the focus group discussion so that essential safety measures could be implemented to enhance road safety.